Communicative-Pragmatic Treatment in Schizophrenia: A Pilot Study - Bosco, Francesca M.; Gabbatore, Ilaria; Gastaldo, Luigi; Sacco, Katiuscia (Frontiers in Psychology, 2016)
This paper aims to verify the efficacy of Cognitive Pragmatic Treatment (CPT), a new remediation training for the improvement of the communicative-pragmatic abilities, in patients with schizophrenia. The CPT program is made up of 20 group sessions, focused on a number of communication modalities, i.e., linguistic, extralinguistic and paralinguistic, theory of mind (ToM) and other cognitive functions able to play a role on the communicative performance, such as awareness and planning. A group of 17 patients with schizophrenia took part in the training program. They were evaluated before and after training, through the equivalent forms of the Assessment Battery for Communication (ABaCo), a tool for testing, both in comprehension and in production, a wide range of pragmatic phenomena such as direct and indirect speech acts, irony and deceit, and a series of neuropsychological and ToM tests. The results showed a significant improvement in patients’ performance on both production and comprehension tasks following the program, and in all the communication modalities evaluated through the ABaCo, i.e., linguistic, extralinguistic, paralinguistic, and social appropriateness. This improvement persisted after 3 months from the end of the training program, as shown by the follow-up tests. These preliminary findings provide evidence of the efficacy of the CPT program in improving communicative-pragmatic abilities in schizophrenic individuals.